2018
DOI: 10.5539/ijbm.v14n1p159
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Diversity and Creativity: The Moderating Effect of Collaborative Climate

Abstract: Creativity is the key for the organizational survival in challenges times. And diversity is one of the factors that could contribute to the creativity. There are many arguments about diversity-performance relationship. however, emphasizing if the cognitive diversity could enhance group creativity? And under which conditions? is still a research gap. The purpose of this research is to examine the cognitive diversity-creativity relationship in the work group. In addition, this research aims to examine the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Organizations adapt various strategies to survive and compete in uncertainty times. Some of these strategies are concerned with organizational processes such as creativity, knowledge management or diversity management (Younis, 2019). These processes are highly related to create a distinguished competitive advantage through its human recourses and human recourses strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Organizations adapt various strategies to survive and compete in uncertainty times. Some of these strategies are concerned with organizational processes such as creativity, knowledge management or diversity management (Younis, 2019). These processes are highly related to create a distinguished competitive advantage through its human recourses and human recourses strategies.…”
Section: Introductionmentioning
confidence: 99%
“…One exception is the study of Martins et al (2013) that reported a positive association between expertness diversity (evaluated as within-group standard deviation of CGPA) and group performance in an IT project realized as part of a course task. Five of the 11 studies that used the summed score of the withingroup standard deviation of cognitive styles reported disruptive effects of cognitive diversity on strategic consensus (Aggarwal & Woolley, 2013, 2019, cohesion and viability (Mello & Delise, 2015), positive emotional states (Armstrong & Priola, 2001), and relationships (Qi & Armstrong, 2019). Overall, these studies showed that horizontal and vertical cognitive diversity co-exist, and vertical cognitive diversity reduces social integration in groups, triggers process losses, and ultimately decreases effectiveness, performance, and creativity.…”
Section: Discussionmentioning
confidence: 99%
“…Higher cognitive group diversity enhanced the indirect effects of knowledge sharing on creativity through knowledge integration and absorptive capacity (Men et al, 2019). Younis (2019) found that a collaborative climate (comprising organizational culture, employee attitude, workgroup support, and immediate supervisor) strengthens the relationship between cognitive diversity and group creativity. X. H. Wang et al (2016) found that cognitive diversity leads to more creativity via group intrinsic motivation only when team leaders exhibit transformational leadership.…”
Section: Topicsmentioning
confidence: 99%
“…This assertion has led researchers to rely heavily on the importance of diverse perspectives where groups pool their diverse information and integrate the collective perspectives to produce innovative solutions (Jehn et al, 1999;Perry-Smith & Shalley, 2003). Diversity has a positive effect on creating novel products and solutions, which is well documented in the literature (see Milliken et al, 2003;Younis, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%